Zero Plastic Campus: Fostering Vision and ‎Mission of Prophetic Values into The Behavior ‎of Campus Community - Saiful Hadi (TADRIS: Jurnal Pendidikan Islam, 2022)
One of the universal values ​​of Islamic education is to establish the human behavior of a learning - friendly environment, especially on campus, through efforts to maintain and keep an environment free from the plastic waste. One of the values is through designing prophetic values ​​on the existing "physical environment" and "social environment" on campus, both elements are a unity that must be designed to be friendly for learning. Establishing individual and group behaviors in maintaining a plastic - free friendly environment is still rarely discussed, particularly from a religious point of view, but some mostly reviewed from the motoric skills of managing plastics point of view. This research reveals the behavior of the academic community of the faculty of tarbiyah about plastic-free environment using participatory design to help build the programs derived from the potential of human resources and other resources in the faculty environment. So that, the behavior of the academic community is "unconscious" of the physical and social environment in the faculty of education IAIN Madura. The results of the research obtained are: a) establishing awareness of the behavior of the academic community in tarbiyah faculty IAIN Madura through; tarbiyah program with integrated zero plastic environment maintenance, zero plastic habituation by leaders to the academic community in tarbiyah, preparation of adequate waste facilities, b) Implementation of zero plastic environment arrange in IAIN Madura tarbiyah faculty with the assistance of waste and plastic materials processing skills, preparation of regulations to reduce and change the plastic materials, include the value of zero plastic in the learning curriculum The suggestions given are a) to the faculty leaders that assistance towards changes in conscious behavior free from plastic materials and waste be done seriously and sustainably, b) to the academic community of IAIN Madura tarbiyah faculty to support unconscious efforts to maintain an environment free from plastic materials and waste.